REGRESI LOGISTIK BINER UNTUK MEMPREDIKSI FAKTOR YANG MEMPENGARUHI NILAI AKHIR PESERTA DIDIK SMK SEPULUH NOPEMBER SIDOARJO DALAM EFEKTIVITAS PEMBELAJARAN PASCA PANDEMI - Yasmin Findi Ariska; Alfisyahrina Hapsery (Statistics Study Programme, Department of Mathematics, Faculty of Mathematics and Natural Sciences, University of Pattimura, 2022)
Education is the awareness to create an environment and learning process that enables students to actively develop the potential for mental strength, self-control, intelligence, noble personality, and abilities needed for themselves and society, which is a directed and planned effort. The quality of education is the most important factor in human development efforts, character growth and competency improvement. Student assessment is an activity that aims to determine the condition of personality and social and spiritual behavior. Therefore we need a statistical modeling to analyze the factors that influence student scores. Data analysis used in this study uses Ordinal Logistic Regression. Ordinal or ranking is a type of data scale that has categorical characteristics where something is better or worse and higher or lower. Ordinal logistic regression is a statistical method for analyzing response variables that have two or more categories and the measurement scale is level. This study shows that the factors that influence the final grades of students at SMK Sepuluh Nopember Sidoarjo include 8 variables, namely gender (female), origin of SMP/MTs (private), everyday language (Javanese), father's occupation (not working), mother's age (36-46 years), number of students (> 35 students), no parental participation, and vocational (non-health) qualifications.